2019
DOI: 10.1002/ajhb.23224
|View full text |Cite
|
Sign up to set email alerts
|

Short sleep and low milk intake are associated with obesity in a community of school aged children from Argentina

Abstract: Objectives Understanding the factors related to obesity during childhood allows for improved preventive actions specifically adapted to particular communities. The purpose of this study was to identify individual and familiar factors related to obesity in children. Methods A cross‐sectional study was conducted in an urban community in Argentina during the years 2015‐2016. Weight and height were measured on a probabilistic sample of 1366 schoolchildren aged 6 to 12 years. BMI categories were established accordi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
10
1
2

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 9 publications
(14 citation statements)
references
References 39 publications
(56 reference statements)
1
10
1
2
Order By: Relevance
“…Therefore, 77 articles were collected as full texts and were further assessed for inclusion. A total of 24 articles were included in the qualitative synthesis, 9,21–31,42–51 and 15 9,22–24,26,28,30,31,39,40,42,43,47,48,51 (which reported risk estimates comparing extreme categories) were included in quantitative synthesis meta‐analyses (Figure S1). Two of the studies (DeBoer et al 9 and Huus et al 26 ) conducted both cross‐sectional and prospective cohort analyses.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Therefore, 77 articles were collected as full texts and were further assessed for inclusion. A total of 24 articles were included in the qualitative synthesis, 9,21–31,42–51 and 15 9,22–24,26,28,30,31,39,40,42,43,47,48,51 (which reported risk estimates comparing extreme categories) were included in quantitative synthesis meta‐analyses (Figure S1). Two of the studies (DeBoer et al 9 and Huus et al 26 ) conducted both cross‐sectional and prospective cohort analyses.…”
Section: Resultsmentioning
confidence: 99%
“…Any disagreement between researchers (MM and LL or IPG and JFGG) was solved by consensus or consulting a third researcher (NB‐T or SKN). When additional information from included articles was required for the analyses, the corresponding author was contacted by e‐mail 21–31 . We received responses from seven authors, 22,24–26 where two provided additional information relevant for inclusion in the analyses 25,31 …”
Section: Methodsmentioning
confidence: 99%
“…31 It has been demonstrated that poor sleep has an effect on the etiopathogenesis of obesity and HTN. 32,33 This study did not establish an association between sleep hours and obesity. However, a positive association was observed between reduced sleep hours and HTN.…”
Section: Discussionmentioning
confidence: 69%
“…In the current study there was a 5% higher incidence of obesity in children not meeting dairy recommendations, which may be a result of the displacement of milk with unhealthier foods/beverages. Orden et al showed, in an Argentine study published in 2019, that low milk consumption was associated with a higher risk of obesity [ 33 ]. It is evident that diet quality needs to be improved in this young population to help decrease the prevalence of obesity and micronutrient inadequacies.…”
Section: Discussionmentioning
confidence: 99%